Pengaruh Kepemimpinan Dan Profesionalisme Kerja Terhadap Prestasi Kerja Guru Pada SMK Negeri 20 Jakarta - Sugiman, Sugiman; Sudarman, Enjang; Priyono, Sigit (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Leadership is someone who has the ability to lead such as strong intelligence, creativity in giving direction to his subordinates. Professionalism comes from the word profession, which means a field of work or position requires certain skills. Job performance is a person's level of proficiency in the tasks that include his or her job. The aim of the research is as follows: To find out whether leadership and work professionalism together influence teacher work performance at SMK Negeri 20 Jakarta.The sampling technique used in this research, the author used the Total Sampling technique or by means of a total population of 72 employees and were sampled using the formula Suharsimi Arikunto, 2017 so there were 72 samples in this research. The positive influence of leadership on teacher work performance obtained a partial value of 0.943, meaning there is a very strong influence or influence with a coefficient of determination of 87.8%. This is proven by testing the hypothesis of the Leadership variable on Teacher Work Performance, with a value of to = 10.718 > t0.05 (70) = 1.661, so Ho is rejected and Ha is accepted, meaning there is a very significant effect. Based on the calculation results, there is a positive influence of Work Professionalism on Teacher Work Performance, a partial value of 0.841, meaning there is a very strong influence or an influence with a coefficient of determination of 70.7%. This is proven by testing the hypothesis of the Work Professionalism variable on Teacher Work Performance, with a value of to = 3.857 > t0.05 (70) = 1.661, so Ho is rejected and Ha is accepted, meaning it has a significant effect. Simultaneously the positive influence of the Leadership and Work Professionalism variables on the Teacher Work Performance variable with a simultaneous correlation value or Summary Model produces an R value of 0.943 and while the R Square value is 0.890 or 89.0%, this can be stated that the results of the analysis together The Leadership and Work Professionalism variables on the Teacher Job Performance variable have a very strong influence. Proven through the results of the Ftest (ANOVA) or Fcount, a value of 279.535 was obtained, which is greater than Ftable (71) of 2.740 with a significance level of 0.000 because 0.000 < 0.05, so it can be said that the variables Leadership and Work Professionalism together or Simultaneously, there is a significant influence on teacher work performance.